Function and development of interneurons involved in brain tissue oxygen regulation - Aksenov, Daniil P.; Gascoigne, David A.; Duan, Jubao; Drobyshevsky, Alexander (Frontiers in Molecular Neuroscience, 2022)
The regulation of oxygen in brain tissue is one of the most important fundamental questions in neuroscience and medicine. The brain is a metabolically demanding organ and its health directly depends on maintaining oxygen concentrations within a relatively narrow range that is both sufficiently high to prevent hypoxia, and low enough to restrict the overproduction of oxygen species. Neurovascular interactions, which are responsible for oxygen delivery, consist of neuronal and glial components. GABAergic interneurons play a particularly important role in neurovascular interactions. The involvement of interneurons extends beyond the perspective of inhibition, which prevents excessive neuronal activity and oxygen consumption, and includes direct modulation of the microvasculature depending upon their sub-type. Namely, nitric oxide synthase-expressing (NOS), vasoactive intestinal peptide-expressing (VIP), and somatostatin-expressing (SST) interneurons have shown modulatory effects on microvessels. VIP interneurons are known to elicit vasodilation, SST interneurons typically cause vasoconstriction, and NOS interneurons have to propensity to induce both effects. Given the importance and heterogeneity of interneurons in regulating local brain tissue oxygen concentrations, we review their differing functions and developmental trajectories. Importantly, VIP and SST interneurons display key developmental milestones in adolescence, while NOS interneurons mature much earlier. The implications of these findings point to different periods of critical development of the interneuron-mediated oxygen regulatory systems. Such that interference with normal maturation processes early in development may effect NOS interneuron neurovascular interactions to a greater degree, while insults later in development may be more targeted towards VIP- and SST-mediated mechanisms of oxygen regulation.